2007
DOI: 10.1073/pnas.0704211104
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of DNA on glycerol nucleic acid templates without stable duplex formation between product and template

Abstract: Glycerol nucleic acid (GNA) is an interesting alternative basepairing system based on an acyclic, glycerol-phosphate backbone repeat unit. The question of whether DNA polymerases can catalyze efficient template-dependent synthesis using GNA as the template is of particular interest because GNA is unable to form a stable duplex with DNA. In the present study, we screened a variety of DNA polymerases for GNA-dependent DNA synthesis. We find that Bst DNA polymerase can catalyze full-length DNA synthesis on a dode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 25 publications
1
66
0
1
Order By: Relevance
“…This strategy worked for cytosine but not for thymine. In a separate study by Szostak, polymerases were also able to use GNA as a template to make DNA [91]. Aminopropyl versions of GNA have also been reported recently, but compatibility with polymerases has not yet been investigated [92].…”
Section: Acyclic Analoguesmentioning
confidence: 99%
“…This strategy worked for cytosine but not for thymine. In a separate study by Szostak, polymerases were also able to use GNA as a template to make DNA [91]. Aminopropyl versions of GNA have also been reported recently, but compatibility with polymerases has not yet been investigated [92].…”
Section: Acyclic Analoguesmentioning
confidence: 99%
“…When used in combinationw ith Kod-RI, an engineered TNA polymerase created by combinatorial librarys creening and scaffold sampling, the aggregate fidelity for acomplete replication cycle of DNA!TNA!DNAi s~1.5 10 À2 ,w hich is slightly higher than one misincorporation per 100 nucleotides. More recently,B st was shown to transcribe and reverse transcribe limited stretches of glyceroln ucleic acid (GNA) polymers, [17,18] as well as copy RNA templatesi nto DNA, [19] suggesting that this enzyme could have broader template specificity than is typical of most naturallyo ccurring DNA polymerases. [12] In that study,t he Geobacillus stearothermophilus DNA polymerase I (Bst) large fragment was identified as one of as mall number of DNA polymerasest hat were capable of extending aD NA primera nnealed to as hort synthetic TNAt emplate with dNTP substrates.…”
mentioning
confidence: 99%
“…The Szostak laboratory recently showed that a GNA region of a DNA-GNA chimeric strand could act as a template for Bst polymerase (Tsai et al 2007). Despite little or no hybridization between GNA and DNA, full-length polymerization of the dodecamer GNA template was achieved.…”
Section: Primitive Genetic Polymersmentioning
confidence: 99%